The Berenstain Bears$1 (Bfunny valentine s - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 2003)
As Valentine$1 (Bs Day approaches, Sister hopes for more attention from one boy and less from another.s
Keywords: Valentine$1 (Bs Days -- Fiction; Bears -- Fiction